Exploring the Potential of Vietnam-Indonesia Relations - Nguyen, Tri Minh; Djuyandi, Yusa; Sudirman, Arfin (Resolusi: Jurnal Sosial Politik, 2025)
The relationship between Vietnam and Indonesia, formally established in 1955, has evolved over seventy years from shared anti-colonial roots into a robust partnership. This journey culminated in the elevation of their ties to a Comprehensive Strategic Partnership (CSP) in March 2025, marking a historic milestone. This article examines the historical trajectory of this relationship, analysing its development through various phases, from early ideological alignment and Cold War complexities to structured cooperation within ASEAN and the Strategic Partnership era (2013-2024). It then delves into the key dimensions of the new CSP, focusing on enhanced cooperation in trade, investment, defence, maritime security, and emerging sectors like the digital and green economies. The article argues that the CSP holds significant untapped potential to deepen bilateral ties, contribute to ASEAN's centrality, and enable both nations to collectively navigate the geopolitical dynamics of the Indo-Pacific. By analysing key milestones, including the crucial 2022 EEZ demarcation, and exploring future opportunities and challenges, the article underscores the strategic importance of this partnership for achieving shared long-term development goals and fostering regional stability.